ANALISIS PERUBAHAN LUAS LAHAN SAWAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
Analysis of changes in wetland area and the factors that influence it in South Ogan Komering Ulu Regency. The purpose of this research is to analyze the change of rice field in South Ogan Komering Ulu Regency. Analyzing the factors affecting changes in wetland area in South Ogan Komering Ulu Regency. The analytical method used is quantitative analysis and supported by qualitative descriptive analysis. To answer the first purpose used mathematical calculations and to answer the second goal used multiple regression analysis.Based on the result of the research, it is concluded that the change of rice field in South Ogan Komering Ulu Regency decreased from year to year with the decreasing rate of 0,929% per year and the factors that have significant effect on the change of land area are the PDRB of agriculture sector, population, and long way.Keyword: Analysis, changes in wetland area, change factor of rice field